Toward sustainable land use planning: Land use mapping for Nandi County, Kenya - Hettiarachchi, Upeksha; Zhang, Wei; Zhe, Guo; Kibet, Walter (CGIAR, 2023)
As part of the Living Labs for People (LL4P) work in Nandi County, Kenya, under the CGIAR Research Initiative on “Low-Emission Food Systems,” researchers from the International Food Policy Research Institute (IFPRI) and the International Livestock Research Institute (ILRI) mapped major land use types in Nandi County using remote sensing and machine learning.